Analysis of the Platform E-Learning Utilization on DSS05 Domain Using the COBIT 5 Framework at Private Universities in Riau Archipelago - Ummul Afifah (Sistemasi: Jurnal Sistem Informasi, 2022)
Most of the private universities in Kepulauan Riau have used the E-Learning system. The increasing use of E-learning has been felt since the COVID 19 Pandemic. Until now there has never been a measurement of the use of E-Learning in Private Universities in Kepulauan Riau using the COBIT 5 Framework. This research was conducted to determine the level of capability of the use of E-Learning in Private Universities in Kepulauan Riau. The focus of this research is on the DSS05 process (Managing Service Security). The results of this study indicate that the level of capability in the DSS05 process reaches level 3, namely the Established Process. The improvement strategy given is the need for improvement in periodic testing of E-Learning and the availability of standard documents related to procedures for regulating the receipt, use, transfer, and disposal of sensitive documents in E-Learning.